(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Kulko V. A. Formation of professional orientation of future ecologists. The article deals with the problem of formation of future specialist professional orientation. On the basis of scientific researches of famous scientists the concept of «personality orientation» is analyzed and the structure of personal professional orientation is considered. The attempt to investigate the main components of future ecologist professional orientation is done.